Peranan Sektor Petanian dalam Pebangunan Ekonomi Regional Provinsi Sumatera Barat - Hilma Kholilah Lubis; Rafika Azwina; Antin Kurnyasih; Niza Utami; Juliana Nasution (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
One of the leading sectors in the economic growth of West Sumatra Province is the agricultural sector. The purpose of this study is to see how the role of the agricultural sector in economic development in West Sumatra Province. The method in this research is descriptive qualitative method. Economic growth in West Sumatra Province can increase, with the assistance of other commodities. Currently, its growth continues to increase, such as the plantation sub-sector, it is estimated that economic growth in West Sumatra this year will be higher than last year. This is of course supported by factors, one of which is technological advances that help the community in knowledge and information that can encourage business fields among the community.